2019
DOI: 10.1038/s41598-019-40816-y
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Ag, Au and Ag-Au bimetallic nanoparticles prepared using golden rod (Solidago canadensis) plant extract

Abstract: Production and use of metallic nanoparticles have increased dramatically over the past few years and design of nanomaterials has been developed to minimize their toxic potencies. Traditional chemical methods of production are potentially harmful to the environment and greener methods for synthesis are being developed in order to address this. Thus far phytosynthesis have been found to yield nanomaterials of lesser toxicities, compared to materials synthesized by use of chemical methods. In this study nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(49 citation statements)
references
References 42 publications
1
44
0
Order By: Relevance
“…As AgNPs are among the most widely used nanomaterial in consumer products, increased use in the food industry has led to public concern regarding their safety and toxicity with long-term use (Chen and Schluesener, 2008;Wijnhoven et al, 2009). Unfortunately, AgNPs can act like a double-edged sword, i.e., they can eliminate bacteria but have also been shown to induce cellular cytotoxicity; in vitro cell culture studies have shown toxic effects of AgNPs in a number of human cell lines (Shi et al, 2018;Botha et al, 2019;Liao et al, 2019). Similarly, in vivo animal studies in rodents have also shown toxic effects of AgNPs due to their accumulation in the liver, spleen, and lung (Alessandrini et al, 2017;Vidanapathirana et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As AgNPs are among the most widely used nanomaterial in consumer products, increased use in the food industry has led to public concern regarding their safety and toxicity with long-term use (Chen and Schluesener, 2008;Wijnhoven et al, 2009). Unfortunately, AgNPs can act like a double-edged sword, i.e., they can eliminate bacteria but have also been shown to induce cellular cytotoxicity; in vitro cell culture studies have shown toxic effects of AgNPs in a number of human cell lines (Shi et al, 2018;Botha et al, 2019;Liao et al, 2019). Similarly, in vivo animal studies in rodents have also shown toxic effects of AgNPs due to their accumulation in the liver, spleen, and lung (Alessandrini et al, 2017;Vidanapathirana et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…If cytotoxicity was assessed, the studies were usually short-term (<5 days), (Panacek et al, 2016;Punjabi et al, 2018) in duration unable to show longer-term cytotoxic effects. Robust data on enhancing antibiotic potential in conjunction with biocompatible doses of AgNPs (Botha et al, 2019) is therefore lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Although these NPs are biocompatible and widely used in different biological applications, there is still demand for the development of other methods that are low cost and easily scalable. In this contribution, the use of plant extracts, being renewable, easy to grow on a mass scale, and environmentally benign, have caught the attention of the researchers [ 14 , 15 , 16 ]. These renewable bio-resources have some advantages, as they minimize the use of surfactants and allow the replacement of organic solvents by water.…”
Section: Introductionmentioning
confidence: 99%
“…Effect of AgNPs against wide range of cancer cell lines was extensively reported. Death of cancer cells was caused by cytotoxic [120], anti-proliferative [41,117], anti-metastatic [121] and apoptotic [122] mechanisms. AgNPs of smaller sizes can freely penetrate into the cells through easy diffusion or pass through receptors, ion channels and transporters across the membrane.…”
Section: Anticancermentioning
confidence: 99%